Dampak Pemasangan Solar Charger Station Pada Pendapatan Masyarakat Sekitar Wisata Pantai Lombang Kabupaten Sumenep - Dessy Novitasari Laras Asih; Very Andrianingsih (PRODI AKUNTANSI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TJUT NYAK DHIEN (UTND), 2024)
Lombang Beach is located in Batang-Batang sub-district, Sumenep Regency. Solar Charger station is a device for charging that uses solar energy. It is hoped that installing a Solar Charger Station on Lombang Beach will increase the income of the surrounding community through increasing tourists. This research aims to evaluate the impact of installing a Solar Charger Station (SCS) on the community's income around the Lombang Beach tourist attraction in Sumenep Regency. The method used in this research is using a qualitative approach. Installing SCS is an effort to support sustainable tourism by utilizing renewable energy. Data was collected through interviews, observation and documentation. The research results show that installing a Solar Charger Station provides benefits in increasing the income of the surrounding community. The Solar Charger Station provides environmentally friendly electrical energy and increases the tourist attraction of Lombang Beach.